Interpreting elevated fetal hemoglobin in pathology and health at the basic laboratory level: new and known γ‐ gene mutations associated with hereditary persistence of fetal hemoglobin. (29th April 2013) - Amato, A.; Cappabianca, M. P.; Perri, M.; Zaghis, I.; Grisanti, P.; Ponzini, D.; Di Biagio, P.
Summary Fetal hemoglobin may be slightly or significantly elevated in post‐natal life due to a number of causes. We report two novel mutations found on the promoter of the Aγ gene and summarize all common and rare determinants associated with hereditary persistence of fetal hemoglobin (HPFH) described thus far. Hematological and molecular analysis of the Aγ globin gene in two cases of HPFH. Comparison of the novel cases with all those described in the literature. We have found two novel mutations in three Italian patients with HbF values between 5.9% and 6.5% without an elevated HbA2 and with normal hemoglobin parameters. In two probands (mother and son), a −197 C>T transition was observed, while in a single individual, a −113 A>G transition was present on the distal CCAAT box of the Aγ gene. As no other abnormalities were present in both γ‐gene promoters and the changes are located on regulatory sequences, we may conclude that these mutations are responsible for the HPFH phenotype shown by the carriers. The laboratory should be able to discriminate between elevated HbF due to artifacts or to serious causes including bone marrow malignancies, aplastic anemia, and β‐thalassemia major or recessive traits such as β‐thalassemia minor, δβ‐thalassemia, or nonpathological conditions induced by mutations or polymorphisms of the γ‐gene promoters that may even be beneficial when present in patients with thalassemia major or sickle cell disease and, in particular, when these patients are treated with hydroxyurea.